Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.5194/bg-4-125-2007
|View full text |Cite
|
Sign up to set email alerts
|

Soils apart from equilibrium – consequences for soil carbon balance modelling

Abstract: Abstract. Many projections of the soil carbon sink or source are based on kinetically defined carbon pool models. Parameters of these models are often determined in a way that the steady state of the model matches observed carbon stocks. The underlying simplifying assumption is that observed carbon stocks are near equilibrium. This assumption is challenged by observations of very old soils that do still accumulate carbon. In this modelling study we explored the consequences of the case where soils are apart fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 52 publications
2
64
0
1
Order By: Relevance
“…5b). This is in line with considerations by Wutzler and Reichstein (2007) who found that for soils that have not reached (and are below) their equilibrium stock, model calibration to the current carbon stock overestimates the decomposition rate of the slowest pool. They propose a transient correction which prescribes a lower decomposition rate for the old pool.…”
Section: Correlations Between Parameterssupporting
confidence: 72%
See 3 more Smart Citations
“…5b). This is in line with considerations by Wutzler and Reichstein (2007) who found that for soils that have not reached (and are below) their equilibrium stock, model calibration to the current carbon stock overestimates the decomposition rate of the slowest pool. They propose a transient correction which prescribes a lower decomposition rate for the old pool.…”
Section: Correlations Between Parameterssupporting
confidence: 72%
“…However, Schmidt et al (2011) proposed that the 14 C content of respired CO 2 and leached dissolved organic carbon could be used as additional constraints in model-data comparisons. Wutzler and Reichstein (2007) have shown that the commonly used equilibrium or steady-state assumption of many SOC models may lead to biased estimates of SOC turnover times. For a soil with SOC stocks below equilibrium, a calibration of turnover times assuming SOC stocks at equilibrium would yield too-fast turnover time estimates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, SOC storage occurs via organic matter accumulation over decades and even millennia. Thus, prior NPP, land fires, and land-use changes may still affect current SOC values (Carvalhais et al, 2008;Wutzler and Reichstein, 2007). Land cover is another important factor, and incorporating the hydrology and resulting carbon dynamics in wetlands may lead to important improvements in ESMs.…”
Section: Identified Influential Factorsmentioning
confidence: 99%